Determinants of Common Mental Disorders (CMD) among adolescent girls aged 15-19 years in Indonesia: Analysis of the 2018 National Basic Health Survey Data. - Muhammad Asrullah; Monique L'Hoir; Maria-João Paulo; Edith J M Feskens; Alida Melse-Boonstra (Public Library of Science (PLoS), 2022)
Common Mental Disorders (CMD) are distress conditions which manifest themselves with anxiety, somatic, and depressive symptoms. CMD are highly prevalent in Indonesia especially among adolescents. Adolescent girls have a higher risk to develop CMD than boys. This may be related to anaemia, potentially aggravated by early onset of menstruation. This study aimed to determine the association between haemoglobin concentration and other determinants of CMD among adolescent girls in Indonesia. Data of 1,052 adolescent girls aged 15-19 years old from the Indonesian Basic Health Survey 2018 were analysed. CMD was measured using the Self Reporting Questionnaire (SRQ-20). Principal Component Analysis of main determinants was applied and resulting principal components were investigated as risk factors for CMD. The prevalence of CMD among the study population was 16.5%. Anaemia and Age at Menarche (AAM) were not associated with CMD. Three principal components were significantly associated with higher CMD score: 1) higher parental education, better employment of the father, and living in an urban area (β: 0.16, 95%-CI: 0.02; 0.30); 2) higher consumption of salty foods, high-fat foods, and soft drinks (β: 0.23, 95%-CI: 0.05; 0.40); and 3) having asthma, smoking, and a higher haemoglobin concentration (β: 1.74, 95%-CI: 1.59; 1.89). The strongest clustered associates of CMD among adolescent girls in Indonesia were asthma, smoking status, and higher haemoglobin concentration, whereas anaemia and AAM were not associated. Causality of smoking and diet to CMD could not be disentangled in this cross-sectional study. Our findings imply that adolescent girls who have asthma and smoke, as well as those having parents with higher education and secured occupation, are more likely to have mental disorders.